Wormhole Attack: a Major Security Concern in Internet of Things (Iot) - Palacharla, Swetha; Chandan, M; GnanaSuryaTeja, K; Varshitha, G (International Journal of Engineering and Technology, 2018)
The Internet of Things (IoT) is nothing but a collection of wireless and wired devices, commonly termed as nodes operated remotely. This operation is done by assuming these nodes as the sensors in a wireless sensor network (WSN) administered through a base station. We start with briefing about IoT and then briefing IoT layer models. After this, we discuss attacks with regard to IoT namely Sinkhole attack, Sybil attack, HELLO flood attack, Acknowledgement spoofing attack and their respective detection methods. This paper is systematic review of existing mechanism for the detection of wormhole attack and a new method is proposed.Â Â